2021
DOI: 10.3390/ijms221910806
|View full text |Cite
|
Sign up to set email alerts
|

CNPase, a 2′,3′-Cyclic-nucleotide 3′-phosphodiesterase, as a Therapeutic Target to Attenuate Cardiac Hypertrophy by Enhancing Mitochondrial Energy Production

Abstract: Heart failure is the end-stage of all cardiovascular diseases with a ~25% 5-year survival rate, and insufficient mitochondrial energy production to meet myocardial demand is the hallmark of heart failure. Mitochondrial components involved in the regulation of ATP production remain to be fully elucidated. Recently, roles of 2′,3′-cyclic nucleotide-3′-phosphodiesterase (CNPase) in the pathophysiological processes of heart diseases have emerged, implicated by evidence that mitochondrial CNPase proteins are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…2′,3′-cAMP is a mitochondrial toxin, and 2-AMP is a neuroprotective agent CNPase can protect oligodendrocytes and axons from injury by reducing the levels of 2′,3′-cAMP and increasing the levels of 2-AMP [52]. A previous study also showed that CNPase can protect mitochondria from AngII-induced metabolic stress [53]. Therefore, in this study, we analysed the mitochondria of oligodendrocytes.…”
Section: Discussionmentioning
confidence: 97%
“…2′,3′-cAMP is a mitochondrial toxin, and 2-AMP is a neuroprotective agent CNPase can protect oligodendrocytes and axons from injury by reducing the levels of 2′,3′-cAMP and increasing the levels of 2-AMP [52]. A previous study also showed that CNPase can protect mitochondria from AngII-induced metabolic stress [53]. Therefore, in this study, we analysed the mitochondria of oligodendrocytes.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of CCL18 [109], SLAMF7 [110], GPR174 [111], CCR4 [112], POU4F2 [113]. CCR2 [114], IL2RB [115], CCL4 [116], CCL24 [117], FASLG (Fas ligand) [118], CD24 [119], TDGF1 [120], CD28 [121], IL7R [122], CYP11B1 [123], CCL5 [124], CCL3 [125], LTF (lactotransferrin) [126], GPNMB (glycoprotein nmb) [127], CD209 [128], IL2RG [129], CHIT1 [130], TAB2 [131], CD163 [132], ALOX15B [133], NMRK2 [134], HGF (hepatocyte growth factor) [135], TRPM8 [136], DIO3 [137], SIGLEC1 [138], TTR (transthyretin) [139], IL24 [140], F13A1 [141], IL9 [142], VEGFA (vascular endothelial growth factor A) [143], RASAL1 [144], ADM (adrenomedullin) [145], ANGPTL4 [146], CHI3L1 [147], LDB3 [148], CNP (2’,3’-cyclic nucleotide 3’ phosphodiesterase) [149], HES6 [150], CMTM5 [151], PLXNB3 [152], KLK8 [153], CDKN1C [154], INSIG1 [155], GREM1 [156], ATF3 [157], HK2 [158], MCAM (melanoma cell adhesion molecule) [159], SEMA4D [160], GLUL (glutamate-ammonia ligase) [161], S1PR5 [162], FN3K [163], MEIS1 [164], ADAMTS4 [165], BIN1 [166], BMP2 [167], LMNA (lamin A/C) [168], ERBB3 [169], DLL1 [170], THBS2 [171], GADD45B [172], MYH6 [173]. PNPLA3 [174], ACTN2 [175], MMP15 [176], SVEP1 [177], CPB2 [178], DYSF (dysferlin) [179], ADAMTSL2 [180], NINJ2 [181], LRP2 [106], PHLDA3 […”
Section: Discussionmentioning
confidence: 99%
“…Another approach to modeling is to simulate the symptoms of the target disease through mutations in genes with known function. Individuals and lines have been created that exhibit analogs of human somatic diseases such as cataract [ 49 , 50 ], myopia [ 51 ], exfoliative syndrome [ 52 ], retinal dysfunction [ 53 , 54 ], congenital heart defect [ 55 ], cardiac hypertrophy [ 56 ], dilated cardiomyopathy [ 57 ], arrhythmia [ 58 ], autoinflammatory syndrome [ 59 ], metabolic syndrome [ 60 ], diabetes and obesity [ 61 ], tuberculosis [ 62 ], thrombocytopenia [ 63 ], pediatric intestinal pseudoobstruction [ 64 ], pediatric cirrhosis [ 65 ], congenital hypothyroidism [ 66 ], fatty or alcoholic hepatosis [ 67 ], and scoliosis [ 68 , 69 ]. Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%